Beneficios de la sutura en procedimientos post extracción. Revisión Bibliográfica - López Araujo, Verónica del Cisne (2022)
The present research work corresponds to a bibliographic review, about the topic: Benefits of suture in post extraction procedures, which seeks to highlight the purpose of the use of sutures insurgical processes. It is accompanied by the analysis of the types and techniques of suture, the types of needle, and the types of thread used in this procedure. The healing process was analyzed, including the types and phases of this physiological process, the risk factors that hindered wound healing, as well as a brief overview of the hemostasis process that plays an important role in the process to suture a wound, as well as the antibiotic therapy used post extraction, The suture of a wound allowed to obtain benefits that were of great importance at the time of achieving a successful closure, thanks to the analysis of several articles, theses and books, which were selected, it was possible to identify the most predominant ones. These benefits are: rapid healing, maintenance of the coagulum, avoidance of tissue dilaceration, anatomical repositioning of the edges and control of hemostasis. The suture materials most commonly used in the surgical field are silk as the thread of first choice, followed by vicryl. Tissue synthesis should be accompanied by a good suturing technique, among which the single and multiple exodontia, the single stitch and the mattress stitch are the first choice techniques